2021
DOI: 10.3390/nu13072360
|View full text |Cite
|
Sign up to set email alerts
|

The Digestibility of Hibiscus sabdariffa L. Polyphenols Using an In Vitro Human Digestion Model and Evaluation of Their Antimicrobial Activity

Abstract: Hibiscus sabdariffa L. (H.s.) is a polyphenolic-rich plant commonly consumed either as a beverage or spice. The aim of the present study was to evaluate the in vitro digestibility of H.s. polyphenols using an in vitro model of digestion which simulates the human stomach and small intestine. The bioaccessible polyphenols released in the digested samples were analyzed by liquid chromatography coupled to photodiode array and mass spectrometry detection. H.s. anthocyanins (cyanidin-3-O-sambubioside and delphinidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Quinic acid production in the intestine can be attributed to the fact that this compound results from the breakdown of hydroxycinnamic acids, such as caffeoylquinic, feruloyl quinic, chlorogenic acids or other similar more complex compounds. A comparable result has also been reported by El Majdoub et al, 2021, where Hibiscus sabdariffa L. (H.s.)…”
Section: Phenolic Profile Of Aqueous and Microencapsulated Extractssupporting
confidence: 90%
See 1 more Smart Citation
“…Quinic acid production in the intestine can be attributed to the fact that this compound results from the breakdown of hydroxycinnamic acids, such as caffeoylquinic, feruloyl quinic, chlorogenic acids or other similar more complex compounds. A comparable result has also been reported by El Majdoub et al, 2021, where Hibiscus sabdariffa L. (H.s.)…”
Section: Phenolic Profile Of Aqueous and Microencapsulated Extractssupporting
confidence: 90%
“…This study also revealed that the absorption of polyphenols is affected during gastrointestinal digestion, which diminishes their digestibility. In addition, in the course of the reduction of some compounds (e.g., caffeoylquinicandcoumaroylquinic acids), quinic acid was produced in the duodenal aliquots [71].…”
Section: Phenolic Profile Of Aqueous and Microencapsulated Extractsmentioning
confidence: 99%
“…This is of special relevance because the biological activity of glycosylated flavonols and cinnamic derivatives, present in cruciferous sprouts, is closely dependent on their bioaccessibility [9]. The decrease in the total content of phenolic compounds after the gastric, intestinal and duodenal phases of action of the digestive process of the plant material, has previously been reported [10,11]. However, the different effect of gastrointestinal digestion on the release and stability of phenolic compounds depends on different factors, such as the physicochemical traits of the food matrix, pH, temperature, or enzymatic activity [12,13].…”
Section: Introductionmentioning
confidence: 90%
“…Different findings were obtained by Majdoub et al [ 40 ]. They noted a decrease in certain compounds after in vitro gastric and duodenal digestion.…”
Section: Resultsmentioning
confidence: 57%